The physical and athletic performance characteristics of Division I collegiate female soccer players by position - Lockie, R. G.; Moreno, M. R.; Lazar, A.; Orjalo, A. J.; Giuliano, D. V.; Risso, F. G.; Davis, D. L.; Crelling, J. B.; Lockwood, J. R.; Jalilvand, F. (The Journal of Strength and Conditioning Research, 2018)
Playing positions in soccer can exhibit different movement demands during a match, contributing to variations in physical and performance characteristics. National Collegiate Athletic Association (NCAA) soccer features different substitution rules when compared to FIFA-sanctioned matches, which could influence each players' characteristics. Therefore, this study determined the athletic performance characteristics of Division I female soccer players. Twenty-six players (3 goalkeepers; 8 defenders; 10 midfielders; 5 forwards) from the same squad completed assessments of: lower-body power (vertical and standing broad jump); linear (0-5, 0-10, 0-30 meter [m] sprint intervals) and change-of-direction (pro-agility shuttle; arrowhead change-of-direction speed test) speed; and soccer-specific fitness (Yo-Yo Intermittent Recovery Test [YYIRT] levels 1 and 2). Players were split into position groups, and a Kruskal-Wallis H test with post hoc pairwise analyses (p = 0.05) calculated significant between-group differences. There were no differences in age, height, or body mass between the positions. Midfielders had a faster 0-5 m time compared with the defenders (p = 0.017) and the goalkeepers (p = 0.030). The defenders (p = 0.011) and midfielders (p = 0.013) covered a greater YYIRT2 distance compared with the goalkeepers. There were no other significant between-position differences. Overall, Division I collegiate female players from the same squad demonstrated similar characteristics as measured by soccer-specific performance tests, which could allow for flexibility in position assignments. However, a relatively homogenous squad could also indicate commonality in training prescription, particularly regarding acceleration and high-intensity running. Strength and conditioning coaches may have to consider the specific movement demands of individual positions when training these capacities.